Comparative analysis of speech impairment and upper limb motor dysfunction in Parkinson's disease - Rusz, Jan; Tykalová, Tereza; Krupička, Radim; Zárubová, Kateřina; Novotný, Michal; Jech, Robert; Szabó, Zoltán; Růžička, Evžen (Journal of neural transmission (Vienna, Austria, 2017)
It is currently unknown whether speech and limb motor effectors in Parkinson's disease (PD) are controlled by similar underlying brain processes. Based on computerized objective analysis, the aim of this study was to evaluate potential correlation between speech and mechanical tests of upper limb motor function. Speech and upper limb motor tests were performed in 22 PD patients and 22 healthy controls. Quantitative acoustic analyses of eight key speech dimensions of hypokinetic dysarthria, including quality of voice, sequential motion rates, consonant articulation, vowel articulation, average loudness, loudness variability, pitch variability, and number of pauses, were performed. Upper limb movements were assessed using the motor part of the Unified Parkinson's Disease Rating Scale, contactless three-dimensional motion capture system, blinded expert evaluation, and the Purdue Pegboard Test. Significant relationships were observed between the quality of voice assessed by jitter and amplitude decrement of finger tapping (r = 0.61, p = 0.003), consonant articulation evaluated using voice onset time and expert rating of finger tapping (r = 0.60, p = 0.003), and number of pauses and Purdue Pegboard Test score (r = 0.60, p = 0.004). The current study supports the hypothesis that speech impairment in PD shares, at least partially, similar pathophysiological processes with limb motor dysfunction. Vocal fold vibration irregularities appeared to be influenced by mechanisms similar to amplitude decrement during repetitive limb movements. Consonant articulation deficits were associated with decreased manual dexterity and movement speed, likely reflecting fine motor control involvement in PD.
Keywords: antiparkinsonika; horní končetina; Speech Disorders; Male; měření tvorby řeči; Bradykinesia; Hypokinetic dysarthria; Limb function; Parkinson’s disease; Speech and voice disorders; Aged; mužské pohlaví; senioři; Severity of Illness Index; Upper Extremity; senioři nad 80 let; lidé; ženské pohlaví; Humans; poruchy řeči; pohybová aktivita; Motor Activity; Aged, 80 and over; Speech Production Measurement; Antiparkinson Agents; Motion capture; stupeň závažnosti nemoci; Female; Parkinson Disease; Parkinsonova nemoc; lidé středního věku; Middle Aged